Gender relations and women's empowerment in small-scale irrigated forage production in the Amhara and SNNP Regions of Ethiopia - Omondi, Immaculate A.; Njuguna-Mungai, Esther; Bezabih, Melkamu; Teufel, Nils; Galiè, Alessandra; Njiru, Nelly; Kariuki, Eunice; Mulema, Annet Abenakyo; Baltenweck, Isabelle; Jones, Christopher S. (2024)
Small-scale cultivation and irrigation of planted forages can increase the availability of good-quality animal feed in smallholder farms. However, low adoption rates of improved forage technologies in most parts of sub-Saharan Africa have been observed and are partly attributed to limited understanding of gender dynamics in the context of production and utilization of planted forages. The introduction of small-scale cultivation and irrigation of planted forages is likely to interlink gender relations in the mixed crop–livestock farming system given the differences in contributions, benefits and challenges men and women farmers face. Efforts to transform livestock systems through improving adoption, scaling, and sustainability forage interventions can benefit from empirical evidence on gender relations in feed-related activities. We aim to highlight the linkage between gender relations and women’s empowerment in the production and utilization of feed resources smallholder settings. We used mixed methods, drawing on quantitative data obtained from a cross-sectional survey of 250 men and 250 women, and qualitative data obtained from eight focus group discussions in smallholder settings of the Amhara and Southern Nations, Nationalities, and People’s regions of Ethiopia, where small-scale irrigation was introduced to boost the production of cultivated forages by households. We used the Women’s Empowerment in Livestock Index tool to elicit data and analyze the empowerment of the sampled men and women. Women’s empowerment differed significantly with different dimensions of gender relations, types of forages grown, and small-scale irrigation practice. Moreover, women in households practicing small-scale irrigation of planted forages were significantly more empowered and most (80%) achieved the adequate threshold in “work balance”. The study findings point to the positive link between empowerment and the likely shifts in gender relations from the practice of small-scale production and irrigation of forages.